EVALUASI PEMBELAJARAN KOLABORATIF MELALUI CREDIT TRANSFER DAN CULTURAL EXCHANGE INTERNASIONAL - Arsyad, M. Fahmi; Ratnasari, Devi; Ayutia, Yolla; Mulyani, Haniva; Sitorus, Sarah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Merdeka Learning Merdeka Campus aims to encourage students to master various fields of science with their fields of expertise, MBKM can provide opportunities for students to gain new learning experiences at other universities in accordance with their study programs so that the graduates produced can meet market demands work both at national and international levels so that the learning process in higher education becomes more autonomous and flexible. The Faculty of Transportation and Logistics Engineering at ITL Trisakti has a credit transfer and cultural exchange program with UniKL MIDI in Malaysia, this program is one of the implementations of the MBKM pre-program at the ITL Trisakti campus, this program was attended by 62 participants from the Environmental Infrastructure Engineering study program ( RIL). As many as 80.7% are interested in participating in the internationalization program in the future, from these data it can be concluded that internationalization activities can increase social networking and knowledge for participants. This research serves to see the extent to which the implementation of MBKM in this case Credit Transfer and Cultural Exchange has been implemented, and to identify any shortcomings that arise from these activities, so that in the future it can become input for the ranks of ITL Trisakti and the Ministry of Education, Culture, Research and Technology. in the implementation of the MBKM program. The author uses quantitative descriptive research methods in assessing the level of participant satisfaction.